Analisis Kebutuhan Lembar Kerja Mahasiswa (LKM) Berbasis Case Method Untuk Menumbuhkembangkan Hots - Amrina, Dian Eka; Budiman, Muhammad Akbar; Simarmata, Ruth Helen (Universitas Hamzanwadi, 2023)
So far, Microeconomics learning has used the case method, but students still experience problems organizing problems in learning. 70% of students have not focused on the problems discussed in lectures because there are no guidelines for solving the problems discussed, so researchers are interested in conducting case method-based student worksheets that need analysis to develop HOTS. This research was conducted using a quantitative descriptive method, the research samples were lecturers who supervised the microeconomics course and 68 students from class 2021 Indralaya Economics Education Study Program, FKIP Universitas Sriwijaya. Data collection techniques were carried out through interviews and questionnaires. The interview data were analyzed using descriptive data and the percentage formula questionnaires. The results of the interviews show that lecturers need to make case method-based student worksheets so that learning is directed at developing HOTS and the result of the questionnaire obtained show that students really need case method-based student worksheets to develop HOTS. This is initial research for developing case method-based student worksheets to develop student HOTS in microeconomics subject